Persepsi Siswa Terhadap Mata Pelajaran IPA Pada SMK Negeri dan Swasta di Kecamatan IV Jurai Kabupaten Pesisir Selatan - Usman, Usman; S, S.Pd.,M.Si, RRP. Megahati; Susanti, Diana (Pendidikan Biologi, 2014)
ABSTRACTÂ SMK is an education that prepares learners to become professionals in accordance with its program expertise. Besides teaching science in vocational education subjects is something new, the previous curriculum vocational subjects did not learn the IPA. From interviews identifiable reason students continue their education at vocational schools is, to develop their talents and interests in membership, students feel less familiar with the material given science teacher. With respect to the purpose of this research is to find a picture of the students perceptions of teaching science in public and private vocational schools in the district of South Coastal District IV Jurai.This study includes a descriptive study. The sample in this study was 20 % of the number of class XI students of public and private vocational schools in District IV Jurai South Coastal District, amounting to 12 students of SMK - Plus Budi Dharma, 37 Person 1 Painan SMK students and 25 students of SMK Negeri 2 Painan. Sampling was done by simple random sampling, while the instrument used for data collection in the form of a questionnaire. The data analysis technique used is the percentage. Student Perceptions of research results Against the IPA Lessons In public and private vocational schools in District IV Jurai South Coastal District shows the percentage of 72.02%, with a sufficient criterion. It can be concluded that students perceptions of teaching science in sufficient criterion.Â